Immune recruitment or suppression by glycan engineering of endogenous and therapeutic antibodies - Le, Ngoc Phuong Lan; Bowden, Thomas A.; Struwe, Weston B.; Crispin, Max (Biochimica et biophysica acta, 2016)
Human serum IgG contains multiple glycoforms which exhibit a range of binding properties to effector molecules such as cellular Fc receptors. Emerging knowledge of how the Fc glycans contribute to the antibody structure and effector functions has opened new avenues for the exploitation of defined antibody glycoforms in the treatment of diseases. Here, we review the structure and activity of antibody glycoforms and highlight developments in antibody glycoengineering by both the manipulation of the cellular glycosylation machinery and by chemoenzymatic synthesis. We discuss wide ranging applications of antibody glycoengineering in the treatment of cancer, autoimmunity and inflammation. This article is part of a Special Issue entitled "Glycans in personalised medicine" Guest Editor: Professor Gordan Lauc. •IgG glycosylation impacts antibody effector function.•Modulation of antibody glycosylation has therapeutic potential.•Antibody glycoforms exhibit anti- and pro-inflammatory properties.